OPTIMIZATION OF ANTHOCYANINS EXTRACTION PROCESS FROM BLACK SOYBEAN SEED COAT FOR THE PREPARATION OF MAIZE-BASED FUNCTIONAL FOOD - Nikolić, Valentina (Journal on Processing and Energy in Agriculture, 2022)
Black soybean seed coat has a considerable content of anthocyanins which can provide a positive effect on the health of the consumers through food products enriched with the extracts of these valuable bioactive compounds. Nevertheless, the use of soybean seed coat, a by-product from soybean processing, additionally valorizes this raw material. The possibility of enrichment of sweet maize grains with anthocyanin extract was investigated. Several procedures with acetic acid were applied in the experiments of anthocyanins extraction from black soybean seed coat. During the marination process, the grains were stained, changing their standard yellow color to a crimson red. Since the brines with the addition of citric acid became cloudy (opalescent) after some time, lactic acid was used as an anthocyanin stabilizer in the continuation of the research. Depending on the extraction conditions, the spectrophotometrically determined content of total anthocyanins in the solution varied from 3541.90 to 5387.70 μg CGE/g d.m., and in the marinated maize grain between 179.89 and 286.05 μg CGE/g d.m. After seven days, the total anthocyanin content in the grain did not increase significantly, so this aging period was selected as optimal for marinating maize products.